Assessing nurses' knowledge and attitudes towards promoting female condom use in South African primary healthcare clinics - Enwongo Ettang; Parimalaranie Yogeswaran; Oladele Vincent Adeniyi (BMC, 2024)
Abstract Background Female condoms protect against unplanned pregnancies and sexually transmitted infections (STIs) including HIV; however, their uptake is very low in South Africa. Nurses are frontline healthcare workers and are uniquely positioned to promote their use to their clients. This study assesses nurses' knowledge of, attitudes to, and practices regarding the promotion of female condoms at selected primary healthcare facilities in the King Sabata Dalindyebo sub-district of the Eastern Cape, South Africa. Methods A descriptive cross-sectional study was conducted from April to May 2021 at five community health centres in the King Sabata Dalindyebo sub-district, South Africa. A total of 139 nurses completed a self-administered questionnaire. Data were analysed using simple descriptive statistics. Results The majority of the participants (82.7%) were knowledgeable about the female condom. Some participants did not have a good attitude and willingness to promote female condom use to their clients. Junior nurses (enrolled nursing assistants and newly qualified professional nurses) were less knowledgeable about the female condom than more qualified and older nurses. There was no significant association between level of knowledge and attitude or willingness to promote the use of the female condom. Conclusion This study found good knowledge of the female condom among the nurses; however, the knowledge did not translate into a willingness to promote the device at their health facilities. Capacity building of the junior nurses will fill the knowledge gaps identified. Studies exploring the sociocultural issues around the female condom are needed in the region.